DIGITAL CRIMINALISATION AND MIGRANT SMUGGLING - RUSU, Ioana-Raluca (International Journal of Legal and Social Order, 2022)
The present article focuses on deep diving into the following four main aspects:1.Crime forms evolution versus societal developments; 2. Distinctions between cybercriminals and criminals and associations related to digitalisation of crime; 3. Software applications and tools enabling or; ganized crime group members to commit various crimes, including migrant smuggling; 4. Impact of technology on crime and possible developments.